Carbodiimide additive to control hydrolytic stability and biodegradability of PLA. (September 2016) - Stloukal, Petr; Jandikova, Gabriela; Koutny, Marek; Sedlařík, Vladimír
Abstract: Enhanced durability of bio-based polylactic acid (PLA) is one of the prerequisites to be a considered as alternative to petroleum-based polymers in long time application. The effect of bis(2, 6-diisopropylphenyl)carbodiimide (BDICDI) additive in various concentration on the extent of hydrolytic stabilization and subsequent degradation kinetics of PLA was studied in the process of abiotic hydrolysis and microbial decomposition under composting conditions. The study showed that BDICDI acts as an efficient stabilizer suppressing the hydrolytic scission of ester bonds of PLA in both degradation processes tested, especially at concentrations above 1.5% w/w. Within the stabilization period which strongly depends on concentrations of BDICDI, suppression of hydrolytic degradation also triggered preservation of thermal and mechanical properties. After the period of stabilization as the dose of stabilizer is depleted, probably via reaction with water molecules and carboxylic groups, the material was hydrolyzed at a comparable or even slightly higher rate than pure PLA. By applying the appropriate amount of BDICDI, the approximate duration of stabilization could be set to suit the desired requirements of the final product.